Mimicking nature to reduce agricultural impact on water cycles: A set of mimetrics. (March 2022) - van Noordwijk, Meine; van Oel, Pieter; Muthuri, Catherine; Satnarain, Usha; Sari, Rika Ratna; Rosero, Paulina; Githinji, Margaret; Tanika, Lisa; Best, Lisa; Comlan Assogba, Gildas Geraud; Kimbowa, George; Andreotti, Federico; et al.
Metrics of hydrological mimicry ('mimetrics') reflect similarity in ecological structure and/or functions between managed and natural ecosystems. Only the land-surface parts of hydrological cycles are directly visible and represented in local knowledge and water-related legislation. Human impacts on water cycles (HIWC) can, beyond climate change, arise through effects on local and regional hydrological processes, from both reduced and increased water use compared to a natural reference vegetation with which landscape structure and hydrology are aligned. Precipitationsheds, the oceanic and terrestrial origin of rainfall, depend on evapotranspiration and thus on vegetation. The political commitment to reduce agricultural impact on nature requires hydrological mimetrics to trickle down through institutions to actions. Existing metrics do not suffice. For example, the water footprint metric that relates agricultural water use to consumption decisions, suggests minimizing water use is best, ignoring full hydrological impacts. We explore principles, criteria and indicators for understanding HIWC, via modified evapotranspiration, effects on streamflow (downstream impacts) and atmospheric fluxes and precipitation (downwind impacts). Comprehensive HIWC mimetrics for a set of pantropical watersheds suggest hydrological mimicry options for forest-derived land use patterns through intermediate densities of trees with diversity in rooting depth and water use, interacting with soils, crops and livestock.